Gradient hole foam catalytic electrode and preparation method thereof
By constructing a gradient-cell foam structure on the electrode, the problem of bubble blockage during electrolysis of water is solved, and the efficiency of electrocatalytic reaction is improved.
Patent Information
- Application Number
- CN202510037973.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing three-dimensional porous electrodes cannot detach the formed bubbles from the inside of the electrode in time when electrolyzing water, resulting in increased resistance, blocked mass transfer and reduced active sites.
The preparation method of gradient pore foam catalytic electrode is adopted to disperse the tiny dispersed in the three-dimensional network foam by gas phase suspension or liquid phase suspension to form a substrate with a gradient pore structure with a large to small distribution of pore sizes, and the electroless plating method is used. The catalyst is plated on its surface.
The high specific surface area of the gradient pore catalytic electrode and good bubble discharge ability are achieved, and the high activity and high gas-liquid mass transfer characteristics are combined, which effectively improves the efficiency of electrocatalytic reactions.
Smart Images

Figure CN119465244A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical catalytic electrodes, and in particular relates to a gradient pore foam catalytic electrode and a preparation method thereof. Background Art
[0002] The catalytic electrode is the core component of the electrocatalytic reaction, and the rational design of the catalytic electrode structure is closely related to its performance. In response to different application scenarios, various forms of electrodes have been developed, including flat electrodes, membrane electrodes, mesh electrodes, and foam structure catalytic electrodes. Among them, the foam structure electrode can effectively promote the occurrence of electrochemical reactions due to its high porosity, high specific surface area, and high active site density. At present, catalytic electrodes are widely used in the fields of chemistry, chemical engineering, energy, biomedicine, and environmental protection.
[0003] Hydrogen production by water electrolysis is a typical electrochemical reaction. With the deepening of energy conservation, emission reduction and the development of renewable energy concepts, hydrogen energy as a clean and efficient energy source has received more and more attention. Hydrogen production by water electrolysis is a clean way to produce hydrogen and has received special attention. In this technical method, efficient catalytic electrodes are a key. Industrial water electrolysis has strict requirements on electrodes, such as high electrochemical activity, tolerance to high current density, resistance to strong chemical corrosion, low gas-liquid mass transfer resistance, high mechanical stability, and long life. Among them, fast reaction kinetics and low bubble mass transfer resistance at high current density are an important bottleneck in the development of electrocatalytic electrodes for practical water electrolysis to produce hydrogen.
[0004] The structure of the electrode is a key factor affecting the performance of industrial practical electrodes. Common electrodes for hydrogen production from water electrolysis and other processes involving gas-liquid mass transfer are metal grid structures with ordered pores. However, metal mesh structures with limited vertical depth are difficult to provide sufficient space for bubble growth, separation, and ion exchange. Three-dimensional porous structures can provide a larger contact area between the catalyst and the electrolyte than planar porous structures, and can reduce the diffusion path of ions and promote the migration of ions inside the substrate. However, at the high current density of industrial water electrolysis, the electrochemical reaction rate is faster, and the reactants will be consumed and hydrogen / oxygen products will be generated at a higher rate. When the gas products cannot quickly leave the electrode, it will cause a serious bubble blocking effect, affecting the charge transfer at the electrode-electrolyte interface and leading to a decrease in activity; violent bubble scouring and gradually increasing internal pressure can easily cause catalyst peeling and reduce stability; in addition, the adhesion of bubbles causes a decrease in the number of electrochemically active sites and an increase in impedance, resulting in an increase in ohmic loss and obstructed mass transfer, which in turn affects the catalytic performance of the catalytic electrode. Therefore, the rational design of the three-dimensional porous structure substrate so that it can not only meet the requirements of sufficient active sites but also separate the formed bubbles from the catalytic electrode in time has important practical value for the development of the field of water electrolysis technology. Summary of the invention
[0005] In view of the problem in the prior art that the three-dimensional porous electrode cannot promptly separate the formed bubbles from the inside of the electrode during the electrolysis of water, thereby causing increased resistance, obstructed mass transfer, and reduced active sites, the present invention proposes a gradient pore foam catalytic electrode and a preparation method thereof. The provided gradient pore catalytic electrode has a high specific surface area and is conducive to the discharge of bubbles, and the preparation method is simple and easy to operate, and is suitable for mass production in industrial preparation.
[0006] In order to achieve the above object, the specific technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing a gradient pore foam catalytic electrode, the specific steps of which are as follows: S1. Gradient dispersion of micro-dispersed materials in a three-dimensional network foam, and stabilization treatment to form a substrate having a gradient pore structure with pore sizes ranging from large to small; S2. The catalyst is plated on the surface of the substrate with gradient pore structure after the stabilization treatment by chemical plating to obtain a porous catalytic electrode with gradient pore structure.
[0007] Preferably, in step S1, the micro-dispersed substance is a polymer material (such as polymethyl methacrylate) or an inorganic non-metallic material (such as silicon dioxide), and has a spherical, linear, flaky, porous structure or a mixed system of multiple morphological structures, and a size between 0.01-100 microns; the three-dimensional network foam is a polymer sponge, foam metal or foam ceramic, and has a mesh size between 0.01-150 microns.
[0008] Preferably, in step S1, the method for gradient dispersion of the micro-dispersed matter is to flow it through a three-dimensional network foam using a gas phase suspension or a liquid phase suspension method, and the network structure formed is an open-pore network structure with gradient pores in at least one dimension, and the pore size distribution is 0.01-150 microns.
[0009] Furthermore, the liquid suspension method comprises mixing the microdispersed matter, the binder and the solvent, ultrasonically dispersing the mixture into a liquid suspension, and pouring the mixture onto the three-dimensional network foam; the concentrations of the microdispersed matter and the binder in the liquid suspension are both 5-100 g•L -1 .
[0010] Furthermore, the gas phase suspension method is to mix the micro-dispersant, the binder and the solvent, ultrasonically disperse them into a gas phase suspension, and spray the suspension onto the three-dimensional network foam through an atomizing spray gun; the flow rate of the atomizing spray gun ranges from 0.5 to 4 mL•s -1 .
[0011] Preferably, in step S1, the stabilization treatment method is heating and curing and / or adhesive curing.
[0012] Preferably, in step S2, the catalyst is one or more of metals, alloys, metal borides, metal phosphides, etc., and the coating thickness is 5-50 microns.
[0013] In a second aspect, the present invention provides a gradient pore foam catalytic electrode prepared by the above preparation method.
[0014] The present invention has the following beneficial effects: The present invention adjusts the size and proportion of micro-dispersed matter and integrates gas phase suspension or liquid phase suspension to construct a gradient pore three-dimensional electrode structure with a high catalyst loading and dense structure on one side of the catalyst layer and a low catalyst loading and loose structure on the other side. The gradient pore catalytic electrode has a high specific surface area and is conducive to bubble discharge. It can combine high activity and high gas-liquid mass transfer characteristics, and can effectively improve the efficiency of the electrocatalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 : Flow chart of the method for preparing the gradient pore catalytic electrode of the present invention.
[0016] Figure 2 : Schematic diagram of the process of stabilization treatment in the method for preparing a foam substrate with a gradient pore structure of the present invention.
[0017] Figure 3 : Schematic diagram of the foam substrate with gradient pore structure in Example 1 and stereomicroscope photograph.
[0018] Figure 4 : SEM image and pore size distribution diagram of the porous catalytic electrode with gradient pore structure in Example 1.
[0019] Figure 5 : Hydrogen evolution performance of water electrolysis using gradient pore catalytic electrode with different amounts of micro-dispersions in Example 1.
[0020] Figure 6 : Oxygen evolution performance of water electrolysis using gradient pore catalytic electrode with different amounts of micro-dispersions in Example 1. DETAILED DESCRIPTION
[0021] The present invention provides a gradient pore foam catalytic electrode and a preparation method thereof to solve the problems of bubble blockage in the existing catalytic electrode and the resulting obstruction of mass transfer and reduction of active sites. The preparation method process is as follows: Figure 1As shown, the gas phase suspension / liquid phase suspension method is innovatively used to composite the micro-dispersed matter with the foam material to construct a gradient pore foam substrate, and then the chemical plating catalyst is used to obtain the gradient pore foam catalytic electrode; the preparation quality of the gradient pore foam substrate is very important, which directly affects the pore distribution, specific surface area, chemical plating difficulty and quality of the electrode. The present invention optimizes the raw material parameters, gas phase suspension / liquid phase suspension process parameters, etc., so that the substrate obtains a high-quality gradient pore structure, overcomes bubble blockage and a series of problems caused by it, and effectively improves the electrochemical performance of the catalytic electrode. The specific steps of the preparation method are as follows: S1. The micro-dispersed substances are made to flow through the three-dimensional network foam by gas phase suspension or liquid phase suspension, and the micro-dispersed substances are dispersed in the three-dimensional network foam in a gradient manner; and the micro-dispersed substances are stabilized by heat curing and / or adhesive curing to form a substrate with a gradient pore structure with pore sizes distributed from large to small. Wherein: The micro-dispersed substances are polymer materials such as polymethyl methacrylate or inorganic non-metallic materials such as silicon dioxide, and have morphologies of spheres, lines, sheets, porous structures or mixed systems of multiple morphologies and structures, with sizes ranging from 0.01 to 100 microns (meaning that the sizes of the materials in all directions are within this range regardless of the morphology); the three-dimensional network foam is a polymer sponge, foam metal or foam ceramic, and has a mesh size of 0.01 to 150 microns; the network structure formed by the gradient dispersion of the micro-dispersed substances in the foam base is an open-pore network structure, having gradient pores in at least one dimension, and the pore sizes are distributed in the range of 0.01 to 150 microns.
[0022] The liquid phase suspension method is to mix the micro-dispersed matter, the binder and the solvent, disperse them into a liquid phase suspension by ultrasonic, and pour them on the three-dimensional network foam; the liquid phase pouring flow rate range is 0.5-4 mL•s -1 The concentrations of the microdispersed matter and the binder in the liquid suspension are both 5-100 g•L -1 In the liquid suspension method, the concentration of microdispersants and binders has a significant effect on the gradient pore structure quality and electrochemical performance of the catalytic electrode.
[0023] The gas phase suspension method is to mix the micro-dispersant, the binder and the solvent, and ultrasonically disperse them into a gas phase suspension, and then spray the suspension onto the three-dimensional network foam through an atomizing spray gun; the flow rate of the atomizing spray gun is in the range of 0.5-4 mL•s -1 The concentration of the microdispersant and the binder in the gas phase suspension is 5-100 g•L -1 In the gas phase suspension method, the flow rate of the suspension controlled by the atomizing gun has a significant effect on the gradient pore structure quality and electrochemical performance of the catalytic electrode.
[0024] S2. The gradient pore structure substrate after the stabilization treatment is loaded with active sites by conventional electrode activation methods (such as physical vapor deposition, solution impregnation reaction, etc.); after activation, the catalyst is plated on its surface by conventional chemical plating process to obtain a porous catalytic electrode with a gradient pore structure. Wherein: the catalyst is one or more of metals, alloys, metal borides, metal phosphides, etc., and the coating thickness is 5-50 microns.
[0025] The following is a specific example of preparing a gradient pore foam catalytic electrode using the above method, which is used to further illustrate the present invention.
[0026] Example 1: Preparation of NiMoB Gradient Pore Catalytic Electrode (1) Pour microdispersed polymethyl methacrylate (PMMA) microspheres and toner C (binder) into ethanol at a certain ratio and disperse them into a liquid suspension by ultrasonication; the concentration of PMMA microspheres in the suspension is 5-20 g•L -1 , toner C concentration is 5-20g•L -1 Specifically, this example tested five concentration groups, including: 0 g•L -1 PMMA-0 g•L -1 Toner C, 5g•L -1 PMMA-5 g•L -1 Toner C, 10•g L -1 PMMA-10 g•L -1 Toner C, 15 g•L -1 PMMA-15 g•L -1 Toner C, 20g•L -1 PMMA-20 g•L -1 Toner C is abbreviated as Without PMMA / C, 5 PMMA / 5 C, 10 PMMA / 10 C, 15 PMMA / 15C, 20 PMMA / 20C.
[0027] (2) The above-mentioned liquid suspensions of different concentrations flow evenly through the melamine foam substrate with an open-pore network structure in the form of liquid suspension, and the liquid pouring flow rate is 4 mL•s -1 , due to gravity, PMMA microspheres and toner C are distributed in a gradient on the foam. Among them, the PMMA / C loading content on the foam skeleton on the tilted surface is high, which reduces the porosity and is recorded as the dense surface; the PMMA / C content on the foam skeleton on the bottom surface is low, which is a high porosity layer and is recorded as the loose surface (such as Figure 3 ).
[0028] (3) The foam substrate on which the microdispersed materials are dispersed in a gradient manner in step (2) is placed in an oven and heated at 120° C. for 10 min to melt the toner C. The toner C acts as a binder to adhere the PMMA microspheres and fix them to the foam substrate. Figure 2 As shown, a foam substrate with a gradient pore structure is obtained.
[0029] (4) Activate the foam substrate with gradient pore structure obtained in step (3), and deposit palladium by physical vapor deposition to load active sites on the gradient pore foam substrate. The physical vapor deposition process of this embodiment is as follows: first, clean the plated part; then use a diffusion pump to evacuate the vacuum chamber to 6×10 -3 Pa background vacuum; then the foam base is bombarded with ions to control the vacuum degree to 10Pa~10 -1 Pa, ion bombardment voltage is 200V~1kV negative high voltage, and ion bombardment time is 5min~30min; finally, the evaporation current is adjusted to melt the palladium and evaporate and deposit it on the foam base.
[0030] (5) Immerse the activated foam substrate with a gradient pore structure obtained in step (4) in a NiMoB chemical plating solution, and obtain a NiMoB catalytic electrode with a gradient pore structure after chemical plating. Optimize the pore distribution of the gradient pore foam substrate by optimizing the suspension concentration in step (2), and then optimize the gradient pore structure of the NiMoB catalytic electrode. Except for the WithoutPMMA / C control group, the four concentration groups successfully formed a gradient pore structure. The best pore structure was obtained when the suspension concentration was 15PMMA / 15C. The average pore size of the dense surface was about 66 µm, and the average pore size of the loose surface was about 108 µm. The morphology and pore size distribution are as shown in FIG. Figure 4 As shown, the gradient range of pores in the optimized gradient pore structure catalytic electrode is 66 μm-108 μm.
[0031] The NiMoB catalytic electrodes with several different gradient pore structures prepared by the above step (2) were used for water electrolysis to test their catalytic hydrogen and oxygen evolution performance. The performance of the series of gradient pore porous electrodes was tested using a three-electrode system. KOH (1 mol•L -1 ) as the electrolyte solution, graphite carbon rod as the counter electrode, mercury / mercuric oxide as the reference electrode, and the prepared gradient pore catalytic electrode as the working electrode. The test results are shown in Figure 5 , 6 As shown. The catalytic performance of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) of the optimized NiMoB catalytic electrodes with several different gradient pore structures has been improved to varying degrees, the reaction overpotential has been reduced, and the reaction energy consumption has decreased. Among them, the current density of the catalytic electrode without gradient pores (Without PMMA / C) is 100mA•cm-2 The hydrogen evolution overpotential at this current density is 136 mV, while the hydrogen evolution overpotential at this current density of the optimized pore structure catalytic electrode (15PMMA / 15C) is only 68 mV, which has been significantly reduced. At the same time, the catalytic activity of oxygen evolution of this electrode also shows the same trend. The current density of the non-gradient pore catalytic electrode is 100 mA•cm -2 The oxygen evolution overpotential at the treatment site is 370 mV, and the current density after treatment is 100 mA•cm -2 The oxygen evolution overpotential at is only 270 mV.
[0032] Example 2: Preparation of NiP Gradient Pore Catalytic Electrode The method is basically the same as Example 1, except that paper fiber (PVA) and toner C (binder) are mixed with ethanol in a certain ratio and dispersed into a liquid suspension by ultrasound; wherein the concentration of paper fiber in the suspension is 5-20 g•L -1 , toner C concentration is 5-20g•L -1 , which corresponds to: 5 g•L -1 PVA-5 g•L -1 C. 10 g L -1 PVA-10 g•L -1 C. 15 g•L -1 PVA-15g•L -1 C. 20g•L -1 PVA-20 g•L -1 C; several groups of concentrations finally prepared NiP catalytic electrodes with different gradient pore structures. Compared with the catalytic electrode without gradient pores, the HER and OER overpotentials were reduced, the reaction energy consumption decreased, and the electrochemical performance was significantly improved. Among them, the NiP catalytic electrode without gradient pores (i.e., the electrode prepared under 0g•L-1 PVA-0g•L-1 C) had a hydrogen evolution overpotential of 187mV and an oxygen evolution overpotential of 411mV at 100 mA•cm-2. The NiP catalytic electrode prepared under the concentration of 10 g•L-1 PVA-10 g•L-1 C had the lowest overpotential, with a hydrogen evolution overpotential of 105mV and an oxygen evolution overpotential of 310mV at 100 mA•cm-2, which was nearly 80mV lower than the hydrogen evolution overpotential of the catalytic electrode without gradient pores, and nearly 100mV lower than the oxygen evolution overpotential of the catalytic electrode without gradient pores.
[0033] Example 3: Preparation of NiFeP Gradient Pore Catalytic Electrode (1) Zeolite powder and copolyester (PA) hot melt powder binder were dispersed in water to form a suspension. The concentration of zeolite powder and copolyester in the suspension was 10 g•L -1 ; The suspension was sprayed onto the nickel foam by an atomizing spray gun; the flow rate range of the atomizing spray gun was 0.5 mL•s-1 to 4 mL•s -1 The above-obtained substrate is further dried in an oven, and after the binder is cured, a nickel foam substrate with a gradient pore structure is obtained.
[0034] (2) Activating the prepared nickel foam substrate with a gradient pore structure, and loading the gradient pore foam substrate with active sites through solution impregnation reaction; the solution impregnation reaction process of this embodiment is as follows: NiSO4·6H2O (0.2 mol·L -1 ) and Me4NB3H8 (0.2 g) are dissolved in 10 mL of deionized water to obtain an activation solution; the foam substrate with a gradient pore structure is immersed in the activation solution at room temperature for 10 minutes, and washed with deionized water to obtain an activated substrate.
[0035] (3) The activated foam substrate with a gradient pore structure is immersed in a NiFeP chemical plating solution to obtain a NiFeP catalytic electrode with a gradient pore structure after chemical plating.
[0036] The results of this example show that the flow rate is 2 mL·s -1 When the substrate with the best gradient structure is obtained, the catalytic electrode prepared has a lower OER overpotential (NiFeP is an oxygen evolution catalyst). The oxygen evolution overpotential of the non-gradient hole NiFeP catalytic electrode (the catalytic electrode prepared by plating NiFeP on pure nickel foam without adding zeolite powder and PA) at 100 mA•cm-2 is 380mV as specified in the manual. The NiFeP gradient hole catalytic electrode prepared at a flow rate of 2mL•s-1 has an oxygen evolution overpotential of 285mV at 100 mA•cm-2, which is nearly 100mV lower than that of the non-gradient hole electrode.
[0037] Example 4: Preparation of Cu Gradient Pore Catalytic Electrode (1) Silica microspheres and polyurethane (TPU) hot melt powder binder were dispersed in water. The resulting mixture was sprayed through an atomizing gun to form a gas phase suspension at a speed of 4 mL•s -1 The flow rate is blown through the through-hole honeycomb ceramic plate; the obtained substrate is heated in a muffle furnace and then cooled to obtain a foam ceramic substrate with a gradient pore structure.
[0038] (2) Activating the prepared ceramic substrate with a gradient pore structure, and using the same method as in Example 3 to load active sites onto the gradient pore foam substrate.
[0039] (3) The activated foam substrate with a gradient pore structure is immersed in a Cu chemical plating solution to obtain a Cu catalytic electrode with a gradient pore structure after chemical plating.
[0040] The above implementation modes are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned implementation modes, a person skilled in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the implementation modes of the present invention.
Claims
1. A method for preparing a gradient pore foam catalytic electrode, characterized in that: The specific steps are as follows: S1. Gradient dispersion of micro-dispersed materials in a three-dimensional network foam, and stabilization treatment to form a substrate having a gradient pore structure with pore sizes ranging from large to small; S2. The catalyst is plated on the surface of the substrate with gradient pore structure after the stabilization treatment by chemical plating to obtain a porous catalytic electrode with gradient pore structure.
2. The method for preparing a gradient pore foam catalytic electrode according to claim 1, characterized in that: In step S1, the micro-dispersed substance is a polymer material or an inorganic non-metallic material, and its morphology is spherical, linear, flaky, porous structure or a mixed system of multiple morphological structures, and its size is between 0.01-100 microns; the three-dimensional network foam is a polymer sponge, foam metal or foam ceramic, and its mesh size is between 0.01-150 microns.
3. The method for preparing a gradient pore foam catalytic electrode according to claim 1, characterized in that: In step S1, the method for gradient dispersion of the micro-dispersed matter is to flow it through a three-dimensional network foam using a gas phase suspension or a liquid phase suspension method, and the network structure formed is an open-pore network structure with gradient pores in at least one dimension, and the pore size distribution is 0.01-150 microns.
4. The method for preparing a gradient pore foam catalytic electrode according to claim 3, characterized in that: In step S1, the liquid suspension method is to mix the micro-dispersed matter, the binder and the solvent, ultrasonically disperse them into a liquid suspension, and pour them onto the three-dimensional network foam; the concentrations of the micro-dispersed matter and the binder in the liquid suspension are both 5-100 g·L -1 .
5. The method for preparing the gradient pore foam catalytic electrode according to claim 3, characterized in that: In step S1, the gas phase suspension method is to mix the micro-dispersant, the binder and the solvent, ultrasonically disperse them into a gas phase suspension, and spray the suspension onto the three-dimensional network foam through an atomizing spray gun; the flow rate of the atomizing spray gun is in the range of 0.5-4 mL•s -1 .
6. The method for preparing a gradient pore foam catalytic electrode according to claim 1, characterized in that: In step S1, the stabilization treatment method is heating and curing and / or adhesive curing.
7. The method for preparing a gradient pore foam catalytic electrode according to claim 1, characterized in that: In step S2, the catalyst is one or more of metals, alloys, metal borides, and metal phosphides, and the coating thickness is 5-50 microns.
8. A gradient pore foam catalytic electrode prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Ceramic foam with gradient of porosity in heterogeneous catalysis
CN102026939A
Method for preparing medical three-dimensional gradient netlike carbon fiber / hydroxyapatite (HA) / medical stone composite material
CN102641522A
Preparation method for high-gradient porous metal film
CN104550980A
Nonmetal substrate high efficiency catalytic electrode and preparation method thereof
CN108624907A
Porous electrode for electrochemical gas production and application of porous electrode
CN110438525A